The pathobiology of vascular dementia - Iadecola, Costantino (2013)
Vascular cognitive impairment defines alterations in cognition, ranging from subtle deficits to full-blown dementia, attributable to cerebrovascular causes. Often coexisting with Alzheimer’s disease, mixed vascular and neurodegenerative dementia has emerged as the leading cause of age-related cognitive impairment. Central to the disease mechanism is the crucial role that cerebral blood vessels play in brain health, not only for the delivery of oxygen and nutrients, but also for the trophic signaling that links inextricably the well being of neurons and glia to that of cerebrovascular cells. This review will examine how vascular damage disrupts these vital homeostatic interactions, focusing on the hemispheric white matter, a region at heightened risk for vascular damage, and on the interplay between vascular factors and Alzheimer’s disease. Finally, preventative and therapeutic prospects will be examined, highlighting the importance of midlife vascular risk factor control in the prevention of late-life dementia.